2016
DOI: 10.1007/s00261-016-0820-x
|View full text |Cite
|
Sign up to set email alerts
|

FDG-PET/CT lymph node staging after neoadjuvant chemotherapy in patients with adenocarcinoma of the esophageal–gastric junction

Abstract: ObjectivesThe aim of the analysis was to assess the accuracy of various FDG-PET/CT parameters in staging lymph nodes after neoadjuvant chemotherapy.MethodsIn this prospective study, 74 patients with adenocarcinoma of the esophageal–gastric junction were examined by FDG-PET/CT in the course of their neoadjuvant chemotherapy given before surgical treatment. Data from the final FDG-PET/CT examinations were compared with the histology from the surgical specimens (gold standard). The accuracy was calculated for fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…Moreover, CRT followed by surgery was shown to be as equally effective as definitive CRT in patients with good PET response, while those with poor PET response had better outcome when surgery follows CRT [12]. In contrast, recent studies showed that FDG uptake characteristics of the primary tumour post neoadjuvant CRT [26,27] and the RLN post neoadjuvant chemotherapy [28] were not able to predict the postoperative histopathological tumour results. A considerable weakness of these studies is that many of them [12,14,[18][19][20][21][22][23][24] included patients with mixed characteristics, i.e., both squamous and adenocarcinoma histology and different treatments, making difficult to draw clinically meaningful conclusions.…”
Section: Discussionmentioning
confidence: 94%
“…Moreover, CRT followed by surgery was shown to be as equally effective as definitive CRT in patients with good PET response, while those with poor PET response had better outcome when surgery follows CRT [12]. In contrast, recent studies showed that FDG uptake characteristics of the primary tumour post neoadjuvant CRT [26,27] and the RLN post neoadjuvant chemotherapy [28] were not able to predict the postoperative histopathological tumour results. A considerable weakness of these studies is that many of them [12,14,[18][19][20][21][22][23][24] included patients with mixed characteristics, i.e., both squamous and adenocarcinoma histology and different treatments, making difficult to draw clinically meaningful conclusions.…”
Section: Discussionmentioning
confidence: 94%
“…Despite increased experience with endoscopic ultrasound (EUS) and positron emission tomography‐CT, in the era of neoadjuvant therapy, the staging accuracy at this tumour stage is not yet satisfactory 42 . One of the great challenges of current imaging modalities is to detect lymph node micrometastasis 43 . In cT2N0M0 patients treated with neoadjuvant chemoradiotherapy, the observed rate of LNM in the surgical resection specimen also remains remarkably high, ranging from 20–50% 18 , 41 , 44 .…”
Section: Discussionmentioning
confidence: 99%
“…However, TGLN metastasis after surgery is the major cause of treatment failure of EC, with an incidence of 12–80% ( 2 5 ), especially the right lymph node metastasis ( 16 , 17 ). The diagnosis of TGLN metastasis is mainly relied on CT and PET-CT scans ( 6 , 18 21 ), where there is a presence of a short diameter ≥0.5 cm and/or high uptake of 18F-PDG ( 22 ). In clinical practice, lymph node metastasis may induce injury of laryngeal nerve, which results in hoarseness and bucking and a poor prognosis.…”
Section: Discussionmentioning
confidence: 99%